Approaches to assessing the impact of robotics in geriatric mental health care: a scoping review. (19th May 2021) - Kulpa, Emily; Rahman, Aniqa T.; Vahia, Ipsit V.
Abstract: The goals of this scoping literature review are to (1) aggregate the current research involving socially assistive robots in the setting of geriatric psychiatry and (2) examine the outcome measures used in these studies and determine where the gaps and needs are. In light of the global COVID-19 pandemic, the geriatric psychiatric population in particular is vulnerable to both the physical and mental toll COVID-19 may cause. Recently, socially assistive robots have gained attention for their ability to aid in the care of the geriatric psychiatry population and are being explored as a realistic way to deliver certain elements of psychiatric care that have the potential to be safe even in the setting of COVID-19. The results of this review indicate that robots are in the early stages of clinical applicability, they display usability for a range of psychiatric indications, and their impact on clinical care is notable. We project that in the next few years, robotic applications will be tailored to address clinical outcomes with a greater degree of precision and efficacy.